KERNOHAN’S NOTCH PHENOMENON IN AN ACUTE COMPONENTED CHRONIC SUBDURAL HEMATOMA PATIENT: A CASE REPORT - Ziya Asan (MNJ (Malang Neurology Journal), 2023)
Kernohan's notch phenomenon is a rare examination finding in cases diagnosed as an intracranial space-occupying lesion. The localization of the space-occupying lesion in this clinical status, which is considered as a sign of herniation, is on the opposite side of the predicted side. The most typical finding is motor deficit and mydriasis on the same side as the space-occupying lesion. A 61-year-old female patient was evaluated in the emergency department due to sudden loss of consciousness. Her neurological examination revealed anisocoria and right hemiparesis findings, including mydriasis in the right pupil. Cranial computed tomography examination revealed a large, acute component combined with chronic subdural hematoma in the right frontoparietal region and midline shift. Clinical and radiological findings were evaluated as Kernohan’s Notch Sign phenomenon. The patient, who was operated on urgently, was discharged on the 7th postoperative day without any neurological deficits.